An Experimental Study on Property Valuation Accuracy in Indonesia: A Government Valuers' Perspective - Prasetyo, Kristian Agung; Riyanto, Edy; Warlan (Yayasan Ilomata, 2025)
Market value estimated by property valuers is essential as it is used for various purposes both in public and private sectors. Hence, the accuracy of market value estimate is of paramount importance. However, valuation involves subjectivity, so it is bound to suffer from errors. This study is aimed at studying such errors. For this purpose, this study uses a market price of a parcel of land in the southern part of Jakarta. This particular area was chosen due to its significant number of property transactions compared to other regions in Jakarta. Government valuers at the Ministry of Finance were invited to provide their value estimate of that property. They were only allowed to use a pre-made worksheet provided by the researchers. This study shows the estimated market value is around 16.9% of the market price. Differences in rank, experience, or neighborhood knowledge have no significant relation to the accuracy of market value estimate. Most participants can demonstrate that their market value estimates are relatively similar, showing low variation between valuers.